Afraid [large type] - Jackson, Lisa (Center Point Large Print, 2022)
"LUCY: Lucy Champagne was sent to St. Cecilia's after her movie-star mother was brutally attacked by her sleazy boyfriend, Ray Watkins. Lucy's damning testimony landed Ray a twenty-five-year sentence. But now, Ray is free. And he's going to find Lucy and make her pay, no matter how far and how fast she runs . . . RAYNE: Rayne Taylor found unexpected happiness at St. Cecilia's, until her roommate, Natalie, committed suicide. Only when Rayne finds a box of mementoes from that time does she realize how wrong she may have been about Natalie's death - and how far someone will go to keep the truth hidden . . . ERIN: Erin MacDonald remembers little about the long-ago night she and her sister, Anna Beth, were kidnapped. While Erin was found safe, Anna Beth vanished forever. Now Erin has reluctantly come back to the family estate, where Detective Rafe Montego hopes to finally crack the case. But as flashes of Erin's memory reemerge, she learns how deep the danger goes."--